Implementasi Video Dokumenter dan Blog Gereja Katolik Kerahiman Ilahi - Yusuf, Yusuf; Junnestine, Junnestine; Wenilya, Feny; Leonardo, Felix (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2019)
This SePORA activity?s intention is to create a product that is expected to help Society. The Catholic Church of Divine Mercy has been our target to observe in Tiban area, Sekupang. We are initiative to donate a product in a form of Documenter Video and Blog which are expected to serve information about the Church in detail. The method we used is a direct observation to the Church for Data Collecting and asked the concerned party for their permission to give us the opportunity of Video taking and interview about the Church?s profile, History and anything that is related to the Church. Subsequently, the data that we have collected will be our material for creating Documenter Video and Blog. As for the results, the Society has understood more about the Catholic Church of Divine Mercy by watching the Documenter Video we have posted on YouTube and also the Blog that have been viewed dozens of times. Build upon the results that we get, we can summarize that Society has known more about the Catholic Church of Divine Mercy by Media Social Platform that we utilize as the medium to promote and to communicate with the Society.